2014
DOI: 10.1016/j.jmir.2013.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Maltese Radiographers' Attitudes towards Continuing Professional Development: An Initial Study Using Concept Maps

Abstract: Purpose: The Council for the Professions Complementary to Medicine in Malta recently published a draft document regarding the introduction of mandatory continuing professional development (CPD) for radiographers. This study explored the attitudes and motivators of Maltese radiographers prior to the implementation of mandatory CPD in order to provide the necessary information required by management to develop CPD successfully. Concept maps are used as part of a methodology to analyse qualitative data.Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…It has been stated however that HEI and CPD pathway postgraduate options remain limited across Europe 44 . There is a real need for stakeholders to improve the development opportunities for Radiographers in both formal HEI settings and in the workplace 35,42,45,46 .…”
Section: Knowledge Skills and Competencymentioning
confidence: 99%
“…It has been stated however that HEI and CPD pathway postgraduate options remain limited across Europe 44 . There is a real need for stakeholders to improve the development opportunities for Radiographers in both formal HEI settings and in the workplace 35,42,45,46 .…”
Section: Knowledge Skills and Competencymentioning
confidence: 99%
“…There were similar findings among radiographers in Sudan, Europe and Australia. [3,9,14,15] Despite the recognised importance of CPD by the participants in this study, they also indicated that they took part in CPD activities owing to mandatory HPCSA requirements. Unfortunately, this is an indicator of a 'tick-box' mentality that was identified in international studies, whereby individuals undertake CPD to fulfil regulatory obligations.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, there are ongoing debates on the effectiveness of mandatory CPD. [14,15] Some international authors recommend that CPD be based on outcomes rather than the number of hours or points attained. [18] While these findings are based on a smaller professional sample, further investigations into whether other professionals display similar attitudes could be valuable for review of the current CPD system.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to other studies which identified a number of barriers to conducting CPD across healthcare professions including staff shortages, cost, time and professional relevance of the activity. [10][11][12][14][15][16][17][18] Departments should consider the limitations RTs and DIs have identified that affect participation in CPD. This will be a challenge for employers as they will have to provide the appropriate resources and opportunities to participate, despite the budgetary pressures.…”
Section: Limiting Factorsmentioning
confidence: 99%